Elaboración de afiches para mejorar la redacción de textos en estudiantes de Primaria - Moreno Bedon, Marylin Kelly (2021)
The present work aims to improve the writing of texts in primary school students, by using the poster as a teaching resource to improve the writing of texts, which is supported by the work entitled Production of posters to improve the writing of texts in primary school students, and which seeks to contribute to the solution of the educational problem in the area of communication and within the framework of the National Basic Education Curriculum (NBEC). It is assumed that the writing of texts is a practical process that is best developed when active resources are used, which not only favour the cognitive aspect, but also the processes of socialization and communication, as well as speed and mental ability, which then becomes an opportunity to improve performance in the competence "Write various types of text in their mother tongue". In this context, it is concluded that the poster, as a teaching resource, allows the improvement of the writing of texts, considering its stimulating, creative and relevant active nature, at the primary level, in particular to strengthen their capacities to adapt the text to the communicative situation, to organise and develop ideas in a coherent and cohesive manner, to use written language conventions in a relevant manner and to reflect and evaluate the form, the content and context of the written text.